Prognostic Value of Various Hemostasis Parameters and Neurophysiological Examinations in Spontaneous Intracerebral Hemorrhage: The IRONHEART Study Protocol - Árokszállási, Tamás; Héja, Máté; Bagoly, Zsuzsa; Kovács, Kitti Bernadett; Orbán-Kálmándi, Rita; Sarkady, Ferenc; Tóth, Judit; Fekete, Klára; Fekete, István; Csiba, László (Frontiers in Neurology, 2021)
Rationale: Stroke is the leading cause of death in all developed countries. In Hungary, more than 10000 patients die annually due to cerebrovascular diseases according to the WHO Mortality Database. 10-15 % of these patients suffer non-traumatic intracerebral hemorrhage (ICH). ICH results in a higher rate of mortality as compared to ischemic stroke and outcomes are difficult to predict. In the GINOP IRONHEART study, we aim to test various hemostasis parameters and clinical neurophysiological examinations in evaluating outcome in intracerebral haemorrhage. Methods: In this prospective, observational study, we plan to enroll consecutive patients with non-traumatic spontaneous intracerebral hemorrhage admitted to a single Stroke Center (Department of Neurology, University of Debrecen, Hungary). The protocol of the GINOP IRONHEART study includes the investigation of detailed clinical, laboratory investigations, and various neurophysiological examiniations. Stroke severity is quantified based on the National Institutes of Health Stroke Scale (NIHSS) on admisson and day 7, 14, 90 after the onset of stroke. Cranial CT is performed on admission, day 14, and 90 to estimate the ICH volume. Modified Rankin Score (mRS) is used for evaluating the long-term outcome (90 days post-event). Blood is drawn immediately on admission for specific hemostasis tests. Digital and quantitative EEG techniques and motor evoked potential (MEP) are performed to evaluate the prognosis of cerebral hemorrhage on admission (within 24-28h), immediately before discharge (10-14 days later), and 3 months after the event. Outcomes: The following outcomes are investigated: 1/ Mortality by day 14 and day 90 2/ Long-term outcome at 90 days post-event: mRS 0-1 is defined as favorable long-term outcome. Discussion: If associations between outcomes and the investigated parameters (hemostasis and neurophysiological examinations) are confirmed, results might aid prognosis assessment in this subtype of stroke with particularly high mortality. Improving clinical grading systems on ICH severity and outcomes by including the investigated parameters could help to better guide the management of these patients in the future.